RT-qPCR profiling of pathogenesis related genes in Musa acuminata cv. 'Berangan' seedlings challenged with Fusarium oxysporum F. SP. Cubense tropical race 4 - Munusamy, Umaiyal; Mohd Yusuf, Yusmin; Baharum, Nadiya Akmal; Zaidi, Kamilatulhusna; Othman, Rofina Yasmin (University of Agriculture, 2019)
The expression profile of pathogenesis related genes are signatures of an infection response in plant cells. Pathogenic infections can increase or reduce gene expression in a plant system in a relatively specific pattern. These expression patterns can be used as standards in pathogenicity studies and, where phenotypic expression is normally used to gauge a plants response to infection, it could additionally present a more rapid and early screening reference tool. Three genes: catalase (CAT), pathogen related protein (PR10), and phenylalanine ammonia (PAL) all implicitly implicated in the plant disease response pathway were targeted for analysis during the infection of Fusarium oxysporum f. sp. cubense tropical race 4 (FOCR4) in banana Musa acuminata cv. Berangan seedlings after a standard challenge under growth room conditions. Distinct patterns of gene expression were observed at three infection time points by real time expression analysis. There was a sequential 10-fold reduction in expression for the PR gene while, the PAL and CAT genes were both upregulated. These results present a set of reference genes that could be used for screening of a plant’s response to Fusarium before the onset of symptoms.